1998
DOI: 10.1103/physrevd.58.083512
|View full text |Cite
|
Sign up to set email alerts
|

Extended inflation with an exponential potential

Abstract: In this paper we investigate extended inflation with an exponential potential V (σ) = V0 e −κσ , which provides a simple cosmological scenario where the distribution of the constants of Nature is mostly determined by κ. In particular, we show that this theory predicts a uniform distribution for the Planck mass at the end of inflation, for the entire ensemble of universes that undergo stochastic inflation. Eternal inflation takes place in this scenario for a broad family of initial conditions, all of which lead… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…To derive the conditions for eternal inflation, we first note that a stochastic differential equation has the general form dX = a(X, t)dt + b(X, t)dW, (30) where a(X, t) is known as the drift coefficient which effects the deterministic evolution of the system, while b(X, t) is known as the dispersion coefficient which introduces random/stochastic fluctuations into the system. Using Eq.…”
Section: The Conditions For Eternal Inflationmentioning
confidence: 99%
See 1 more Smart Citation
“…To derive the conditions for eternal inflation, we first note that a stochastic differential equation has the general form dX = a(X, t)dt + b(X, t)dW, (30) where a(X, t) is known as the drift coefficient which effects the deterministic evolution of the system, while b(X, t) is known as the dispersion coefficient which introduces random/stochastic fluctuations into the system. Using Eq.…”
Section: The Conditions For Eternal Inflationmentioning
confidence: 99%
“…Linde and Linde [29] investigated the global structure of an inflationary universe both by analytical methods and by computer simulations of stochastic processes in the early universe. Susperregi and Mazumdar [30] considered an exponential inflation potential and showed that this theory predicts a uniform distribution for the Planck mass at the end of inflation, for the entire ensemble of universes that undergo stochastic inflation. Vanchurin, Vilenkin, and Winitzki [31] investigated methods of inflationary cosmology based on the Fokker-Planck equation of stochastic inflation and direct simulation of inflationary spacetime.…”
Section: Introductionmentioning
confidence: 99%
“…(6 and 12-13) while the conservation equations are defined by Eqs (20)(21). The solution behaves as (22), therefore we have obtained the following solution a 1 = a 2 = a 3 = 1, q = 0, ∀m ∈ (−1, 1) \ {0} , so the metric collapses to Eq. (48), i.e.…”
Section: Non-interacting Scalar and Matter Fields With G-varmentioning
confidence: 90%
“…(6 and 12-13) and the corresponding conservation equations given by Eqs (20)(21). The solution behaves as (22), therefore we have obtained the following solution…”
Section: Non-interacting Scalar and Matter Fields With G-varmentioning
confidence: 98%
“…Linde and Linde [LL94] investigated the global structure of an inflationary universe both by analytical methods and by computer simulations of stochastic processes in the early universe. Susperregi and Mazumdar [SM98] considered an exponential inflation potential and showed that this theory predicts a uniform distribution for the Planck mass at the end of inflation, for the entire ensemble of universes that undergo stochastic inflation. Vanchurin, Vilenkin, and Winitzki [VVW00] investigated methods of inflationary cosmology based on the Fokker-Planck equation of stochastic inflation and direct simulation of inflationary spacetime.…”
Section: Introductionmentioning
confidence: 99%